2016
DOI: 10.1016/j.niox.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and removal of impurities in nitric oxide generated from air by pulsed electrical discharge

Abstract: Inhalation of nitric oxide (NO) produces selective pulmonary vasodilation without dilating the systemic circulation. However, the current NO/N2 cylinder delivery system is cumbersome and expensive. We developed a lightweight, portable, and economical device to generate NO from air by pulsed electrical discharge. The objective of this study was to investigate and optimize the purity and safety of NO generated by this device. By using low temperature streamer discharges in the plasma generator, we produced thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We found that all the murine airway tissues, including tracheobronchial tissue and tissue of the distal lung, from both control (breathing air only) and mice breathing 50 ppm electric NO were normal and free of metal particles. (46) Taken together, these results indicate that prolonged inhalation of electrically generated NO is safe.…”
Section: No For the Treatment Of Pulmonary Hypertensionmentioning
confidence: 75%
See 2 more Smart Citations
“…We found that all the murine airway tissues, including tracheobronchial tissue and tissue of the distal lung, from both control (breathing air only) and mice breathing 50 ppm electric NO were normal and free of metal particles. (46) Taken together, these results indicate that prolonged inhalation of electrically generated NO is safe.…”
Section: No For the Treatment Of Pulmonary Hypertensionmentioning
confidence: 75%
“…Applying scanning electron microscopy and energy-dispersive X-ray spectroscopy, we detected and determined the metal particles (iridium, platinum, and nickel) released from the electrodes after plasma NO generation. (46) We then tested whether a 0.22 lm high-efficiency particular air (HEPA) filter, placed in series with the NO generator, could capture all the metal particles in the effluent gas stream. Our data suggest that one single HEPA filter can effectively remove all metal particles released from the electrodes when generating electric plasma NO.…”
Section: No For the Treatment Of Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential limitation of the mini-NO generator might be that the electrically generated NO is contaminated with trace metals. Because iridium electrodes slowly erode while generating NO [31], and the alloy holders of the electrodes may contribute small amounts of nickel and platinum, we examined the effluent gas stream for trace metal particles. With an inline Ca(OH) 2 (0.8 g) scavenger and a single HEPA filter, the electrodes released 0.018 μg/day of nickel in a 24-hr period, which is far below OSHA’s safety standards.…”
Section: Resultsmentioning
confidence: 99%
“…We selected iridium electrodes for NO generation to reduce the level of NO 2 when compared to other metal electrodes. Using a 12-g scavenger, we removed NO 2 and O 3 , and demonstrated that the electrical plasma NO generator stably produces safe therapeutic levels of inhaled NO from air [3]. Recently, we have developed a novel miniaturized version of the device for an infant, weighing about 14-g and safely producing therapeutic levels of NO from air [4].…”
mentioning
confidence: 99%